2004
DOI: 10.1074/jbc.m406637200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Sequence Surrounding Predicted Transmembrane Helix M4 in Membrane Association and Function of the Ca2+ Release Channel of Skeletal Muscle Sarcoplasmic Reticulum (Ryanodine Receptor Isoform 1)

Abstract: The role of the sequence surrounding M4 in ryanodine receptors (RyR) in membrane association and function was investigated. This sequence contains a basic, 19-amino acid M3/M4 loop, a hydrophobic 44 -49 amino acid sequence designated M4 (or M4a/M4b), and a hydrophilic M4/M5 loop. Enhanced green fluorescent protein (EGFP) was inserted into RyR1 and truncated just after the basic sequence, just after M4, within the M4/M5 loop, just before M5 and just after M5. The A52 epitope was inserted into RyR2 and truncated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…1B) further defined the boundaries of the six TM segments of RyR1. The boundaries of the TM segments combined with the known luminal or cytosolic location of intervening loops in between the TM segments (1,48) enabled us to propose a TM topology for RyR1 (Fig. 1C), which underscores its similarity to the known structures of 6-TM cation channels (15, 23, 49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) further defined the boundaries of the six TM segments of RyR1. The boundaries of the TM segments combined with the known luminal or cytosolic location of intervening loops in between the TM segments (1,48) enabled us to propose a TM topology for RyR1 (Fig. 1C), which underscores its similarity to the known structures of 6-TM cation channels (15, 23, 49).…”
Section: Resultsmentioning
confidence: 99%
“…1A) in the RyR1 C-terminal region (residues 4561-4948; UniProt accession number P11716). The presence of the six membrane-spanning segments is sufficient to support RyR1 ion channel activity as seen by single channel recordings of tryptic fragments (47) and deletion of the preceding putative TM segments (48). Overlaying the TM prediction on secondary structure prediction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A. Substantial additional attempts to resolve the topology of this region (26) failed to demonstrate the presence of a pair of TMD before TMD1, suggesting that the region may be associated with the membrane without integrating into it. The latter is consistent also with three-dimensional reconstructions of cryoelectron microscopic images of RyR1.…”
mentioning
confidence: 99%
“…Channel conduction has been localized to the C-terminal fifth of the protein by truncation (Bhat et al, 1997). Bioinformatics (Shah and Sowdhamini, 2001;Williams et al, 2001) and extensive mu-tational studies have further identified putative channel elements of RyRs (Zhao et al, 1999;Gao et al, 2000;Du et al, 2001Du et al, , 2004Chen et al, 2002;Wang et al, 2003Wang et al, , 2004. Most recently, a 3D model of the RyR pore (Welch et al, 2004) has been proposed derived from structural analogies with the known X-ray structure of the prokaryotic K ϩ channel KcsA (Doyle et al, 1998).…”
mentioning
confidence: 99%
“…Extensive alanine scanning of these putative pore-forming domains of RyRs has identified several residues that abolish [ 3 H]ryanodine binding (Zhao et al, 1999;Gao et al, 2000;Du et al, 2001Du et al, , 2004Chen et al, 2002;Wang et al, 2003Wang et al, , 2004. Those that retain caffeine sensitivity, implying a lack of gross distortion of structure, but abolish ryanodine-sensitivity indicate a clear effect on the ryanodine binding site (Wang et al, 2003).…”
mentioning
confidence: 99%